Policing transnational crime law enforcement of criminal flows - Hufnagel, Saskia; Moiseienko, Anton (Transnational criminal justice, 2020)
"The volume invites reflection on whether the existing tool kit of governments and law enforcement agencies is adequate in this changing environment and how it could be modernised, for example, by increased reliance on technology or by reappraising the role of the private sector. As such, the book will be useful not only for academics and practitioners who work on security-related matters, but also more generally to those who are interested in what the near-term future of policing is likely to look like and how the balance between law enforcement on the one hand and human rights and civil liberties on the other can be achieved"